A general strategy to achieve ultra-high gene transfection efficiency using lipid-nanoparticle composites - Vankayala, Raviraj; Chiang, Chi-Shiun; Chao, Jui-I; Yuan, Chiun-Jye; Lin, Shyr-Yeu; Hwang, Kuo Chu (My University, 2014)
Gene therapy provides a new hope for previously "incurable" diseases. Low gene transfection efficiency, however, is the bottle-neck to the success of gene therapy. It is very challenging to develop non-viral nanocarriers to achieve ultra-high gene transfection efficiencies. Herein, we report a novel design of "tight binding-but-detachable" lipid-nanoparticle composite to achieve ultrahigh gene transfection efficiencies of 60 similar to 82%, approaching the best value (similar to 90%) obtained using viral vectors. We show that Fe@CNPs nanoparticles coated with LP-2000 lipid molecules can be used as gene carriers to achieve ultra-high (60-80%) gene transfection efficiencies in HeLa, U-87MG, and TRAMP-C1 cells. In contrast, Fe@CNPs having surface-covalently bound N,N,N-trimethyl-N-2-methacryloxyethyl ammonium chloride (TMAEA) oligomers can only achieve low (23-28%) gene transfection efficiencies. Similarly ultrahigh gene transfection/expression was also observed in zebrafish model using lipid-coated Fe@CNPs as gene carriers. Evidences for tight binding and detachability of DNA from lipid-nanoparticle nanocarriers will be presented. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Gene transfection; Gene therapy; Nanocarriers; Zebrafish; Cytotoxicity; Carbon nanoparticles